2011
DOI: 10.1523/jneurosci.6032-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fatigue Affects Mental Simulation of Action

Abstract: Several studies suggest that when subjects mentally rehearse or execute a familiar action, they engage similar neural and cognitive operations. Here, we examined whether muscle fatigue could influence mental movements. Participants mentally and actually performed a sequence of vertical arm movements (rotation around the shoulder joint) before and after a fatiguing exercise involving the right arm. We found similar durations for actual and mental movements before fatigue, but significant temporal discrepancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 42 publications
6
48
0
Order By: Relevance
“…This sensory feedback cannot be applied to IM, therefore they remained unchanged in 0G. This is consistent with a recent study showing that imagined arm movement durations are increased immediately after muscular fatigue and that the durations return to normal prefatigue values after a longer delay than the actual arm movement durations (Demougeot and Papaxanthis, 2011). These authors stated that the delay in adaptation of imagined arm movement durations is the result of the absence of sensory feedback and that state estimation derives from forward model alone, the brain continues to simulate faster mental movements after fatigue based on inappropriate neural drives.…”
Section: Updating Internal Models Under Short-term 0gsupporting
confidence: 90%
“…This sensory feedback cannot be applied to IM, therefore they remained unchanged in 0G. This is consistent with a recent study showing that imagined arm movement durations are increased immediately after muscular fatigue and that the durations return to normal prefatigue values after a longer delay than the actual arm movement durations (Demougeot and Papaxanthis, 2011). These authors stated that the delay in adaptation of imagined arm movement durations is the result of the absence of sensory feedback and that state estimation derives from forward model alone, the brain continues to simulate faster mental movements after fatigue based on inappropriate neural drives.…”
Section: Updating Internal Models Under Short-term 0gsupporting
confidence: 90%
“…Looking at the selective effect of physical fatigue on IVI and EVI however revealed that both MI duration and vividness were substantially affected when athletes used IVI, whereas there was no actual influence of fatigue when performing EVI. These data suggest that the effect of physical fatigue on MI ability is dependent on imagery content, and might therefore not be due to a general perception of muscular fatigue, as earlier postulated by Demougeot and Papaxanthis [36]. These results further promote the importance of taking the MI perspective into account when studying this mental process.…”
Section: Discussionsupporting
confidence: 75%
“…Action representation is generated by an internal forward model, which is a neural network that simulates the dynamic behavior of the body and its interaction with the environment [16], [27], [50], [56]. Theoretically, when participants imagine arm movements, the forward model relates the actual state of the arm (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The participants, using their right arm, were requested to actually move or mentally simulate moving (imagined movement) at a natural self-selected speed between the CT and RT or between the CT and LT. Actual and mental trials were performed with eyes open. It is known that relatively long trial durations are necessary to obtain reliable measurements in motor imagery protocols because movement durations have a coarse resolution [16], [50]. Therefore, in our protocol one trial corresponded to three successive and fluid arm movements between the CT and the other targets: CT-RT-CT-RT-CT-RT-CT and CT-LT-CT-LT-CT-LT-CT. For the actual trials, participants were asked to move their arm over the table without touching it.…”
Section: Methodsmentioning
confidence: 99%